Identification of infectious agents in onychomycoses by PCR-terminal restriction fragment length polymorphism - Verrier, Julie; Pronina, Marina; Peter, Corinne; Bontems, Olympia; Fratti, Marina; Salamin, Karine; Schürch, Stéphanie; Gindro, Katia; Wolfender, Jean-Luc; Harshman, Keith; Monod, Michel (Journal of clinical microbiology, 2012)
A fast and reliable assay for the identification of dermatophyte fungi and nondermatophyte fungi (NDF) in onychomycosis is essential, since NDF are especially difficult to cure using standard treatment. Diagnosis is usually based on both direct microscopic examination of nail scrapings and macroscopic and microscopic identification of the infectious fungus in culture assays. In the last decade, PCR assays have been developed for the direct detection of fungi in nail samples. In this study, we describe a PCR-terminal restriction fragment length polymorphism (TRFLP) assay to directly and routinely identify the infecting fungi in nails. Fungal DNA was easily extracted using a commercial kit after dissolving nail fragments in an Na(2)S solution. Trichophyton spp., as well as 12 NDF, could be unambiguously identified by the specific restriction fragment size of 5'-end-labeled amplified 28S DNA. This assay enables the distinction of different fungal infectious agents and their identification in mixed infections. Infectious agents could be identified in 74% (162/219) of cases in which the culture results were negative. The PCR-TRFLP assay described here is simple and reliable. Furthermore, it has the possibility to be automated and thus routinely applied to the rapid diagnosis of a large number of clinical specimens in dermatology laboratories.